(4m+5):(3m+7)=13:17
We can write it as,
(4m+5)/(3m+7)=13/17
Multiplying by equal factors on both sides,
{(4m+5)×(4m-5)}/{(3m+7)×(3m-7)}=13(4m+5)/17(3m-7)
After simplifying we get a cubic equation as,
348m^{3} -1319m^{2}-1273m-210=0
solving the cubic equation we get,
m_{1}=23/5, m_{2}=3/5, m_{3}=2/9
(4m+5):(3m+7)=13:17
we can solve it various we use simplest method
product of mean = product of extreme
17(4m + 5) = 13(3m + 7)
68m + 85 = 39m + 91
now we change their places to make same variable one side and numbers the other side
68m - 39m = 91 - 85 ( change their sign after change places as rule of alternate signs )
29m = 6
m = 6/29 Ans